Multicentre study of short‐course radiotherapy, systemic therapy and resection/ablation for stage IV rectal cancer. Issue 5 (3rd February 2020) - Kok, E. N. D.; Havenga, K.; Tanis, P. J.; de Wilt, J. H. W.; Hagendoorn, J.; Peters, F. P.; Buijsen, J.; Rutten, H. J. T.; Kuhlmann, K. F. D.; ,
Abstract : Background: The optimal treatment sequence for patients with rectal cancer and synchronous liver metastases remains unclear. The aim of this study was to evaluate the feasibility and effectiveness of short‐course pelvic radiotherapy (5 × 5 Gy) followed by systemic therapy and local treatment of all tumour sites in patients with potentially curable stage IV rectal cancer in daily practice. Methods: This was a retrospective study performed in eight tertiary referral centres in the Netherlands. Patients aged 18 years or above with rectal cancer and potentially resectable liver ± extrahepatic metastases, treated between 2010 and 2015, were eligible. Main outcomes included full completion of treatment schedule, symptom control and survival. Results: In total, 169 patients were included with a median follow‐up of 49·5 (95 pr cent c.i. 43·6 to 55·6) months. The completion rate for the entire treatment schedule was 65·7 per cent. Three‐year progression‐free survival and overall survival (OS) rates were 24·2 (95 per cent c.i. 16·6 to 31·6) and 48·8 (40·4 to 57·2) per cent respectively. Median OS of patients who responded well and completed the treatment schedule was 51·5 months, compared with 15·1 months for patients who did not complete the treatment ( P  < 0·001). Adequate symptom control of the primary tumour was achieved in 87·0 per cent of all patients. Conclusion: Multimodal treatment leads to relief of symptoms in most patients, and is associated with good survival rates in those able to complete the schedule. [Correction added on 12 February 2020, after first online publication: the Conclusion has been reworded for clarity] Abstract : Treatment of patients with potentially curable stage IV rectal cancer with short‐course pelvic radiotherapy followed by systemic therapy and local treatment of all tumour sites is a feasible and effective schedule. Long‐term survival was accomplished in one‐third of patients, while providing adequate symptom relief in the majority of the other patients. Good results Abstract : Antecedentes: La secuencia óptima de tratamiento en pacientes con cáncer de recto y metástasis hepáticas sincrónicas sigue sin estar clara. El objetivo de este estudio fue evaluar en la práctica diaria la viabilidad y efectividad de la radioterapia pélvica de ciclo corto (5 x 5 Gy) seguida de tratamiento sistémico y tratamiento local de todas las localizaciones del tumor primario en pacientes con cáncer de recto estadio IV potencialmente curables. Métodos: Estudio retrospectivo realizado en ocho centros terciarios de referencia en Holanda. Se consideró elegibles a los pacientes mayores de 18 años con cáncer de recto y metástasis hepáticas ± extrahepáticas potencialmente resecables, que fueron tratados entre 2010 y 2015. Los criterios de valoración principales incluyeron la finalización completa del programa de tratamiento, el control de los síntomas y la supervivencia. Resultados: En total se incluyeron 169 pacientes con una mediana de seguimiento de 50 meses (rango 2‐89 meses). La tasa de finalización del programa de tratamiento completo fue del 65, 7%. Las tasas de supervivencia libre de progresión a 3 años y supervivencia global ( overall survival, OS) fueron 24, 2% (i.c. del 95% 16, 6‐31, 6) y 48, 8% (i.c. del 95% 40, 4‐57, 2), respectivamente. La mediana de OS de los pacientes que respondieron bien y completaron el programa de tratamiento fue de 51, 5 meses, en comparación con 15, 1 meses en pacientes que no completaron el tratamiento ( P < 0, 001). Se logró un control adecuado de los síntomas del tumor primario en el 87, 0% de todos los pacientes. Conclusión: El tratamiento multimodal consigue paliar los síntomas en la mayoría de los pacientes y se asocia con buenas tasas de supervivencia en aquellos pacientes que pueden completar el programa.